Repercussion of lactic bacteria and yeasts on the productive performance and health of piglets - Miranda-Yuquilema, José E. (2018)
The objective of this study was to evaluate the effect of two microbial preparations on the productive performance, health and blood profile of piglets. In total, 120 piglets (Duroc x Yorkshire/Landrace) offspring of 12 breeding sows (Landrace/Yorkshire) were distributed in three groups of 40 animals each under a completely randomized design: control (T1); Bioprepared (T2) and Biopreparared (T3). T2 contained Lactobacillus acidophilus and Streptoccus thermophilus and T3 Saccharomyces cerevisiae and Kluyveromyces fragilis (L-4 UCLV). Birth weight and body weight and body weight gain (BWG) on days 14 and 33 (weaning) of age, incidence of diarrhoea and blood and biochemical profiles were evaluated. The birth weight and the BWG of piglets of T2 and T3 was greater than in the piglets of the control group (p<0.05), without difference between T2 and T3. The occurrence of diarrhoea was reduced by 52% in the animals treated with the probiotics. The hematochemical profile differed between treatments (p<0.05). It is concluded that the use of lactic-acid bacteria and yeast produced a positive effect on the productive performance, health, and blood profile in piglets.